Just Transition Process: Green Jobs as Instruments for Implementation - Sierra Hernaiz, Elisa (2023)
Nowadays, one of the most important changes in global society is providing responses to the effects of climate changes. In this context is essential to start social, economic, financial, ecological or training public politics to guarantee that the result of the Just Transition Process does not give rise to new inequalities or perpetuate existing ones, especially for the most vulnerable social groups, as young people, women or unemployed people. Despite the fact that current world situation does not facilitate its implementation, this cannot be an obstacle to ignoring it given the magnitude of climate change. Regarding its impact on the labor market, characterized by with workforce transitions and new sources of employment, green jobs are the appropriate instrument, with tree main challenges to guarantee its success. Firstly, it is necessary to adopt professional training policies to get new professional skills, especially in new digital technologies. Secondly, is necessary to incorporate the gender perspective in all phases to avoid perpetuating women’s inequalities. Finally, social dialogue must be the central